The Effect of Motivation, Working Environment and Discipline on Employee Performance: The Case of South Sumatera Regional House of Representative Secretariat - Reza Kurnia Pratama; Abid Djazuli; Choiriyah Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to determine 1) the influence of motivation, work environment, and work discipline on the performance of employees in the Secretariat of the Regional People's Representative Council of South Sumatra Province. 2) The influence of motivation on the performance of employees in the Secretariat of the Regional People's Representative Council of South Sumatra Province. 3) The Influence of the Work Environment on the Performance of Employees at the Secretariat of the Regional People's Representative Council of South Sumatra Province. 4) The Influence of Work Discipline on the Performance of Employees at the Secretariat of the Regional People's Representative Council of South Sumatra Province. This research was associative. The population of this study comprised all 224 employees; the sample comprised 142 employees, and the sampling technique was cluster sampling. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was multiple linear regression in SPSS. The results of this study indicate that: 1) there is a significant influence of motivation, work environment, and work discipline on employee performance. 2) There is a significant influence of motivation on employee performance. 3) There is a significant influence of the work environment on employee performance. 4) There is a significant influence of work discipline on employee performance.